A User-Centered Framework for the Design of Usable ATM Interfaces - Aguirre, Joel (2019)
Nowadays, the design of usable interfaces is a challenge for every software developer. Little or no consideration of the user-centered design guidelines make systems difficult to use, and the embedded systems in the Automated Teller Machines (ATM) are not an exception to this problem. In order to improve and ensure the usability of the user interfaces of software in this domain, several user-centered design methods and techniques were analyzed and applied to formulate a framework for guiding a design process. The paper provides an analysis of a variety of methods used in the self-service technologies domain and by formal design methodologies; for instance, the standard ISO 13047. In addition, the article describes the process followed to select the most appropriate user-centered design methods that fit the specific ATM domain. This analysis includes surveys and expert judgment, conducted with ATM and usability experts, which show a correct selection of the methods.